Collaborative Governance Penerapan Collaborative Governance Sebagai Strategi Inovasi Pelayanan Publik Digital di Mal Pelayanan Publik Kota Jambi - fardila, vonny; Yusri Maulana, Rio; Al Kausar, Jefri (Jurnal Administrasi Publik dan Bisnis, 2026)
This study analyzes the implementation of collaborative governance as an innovation strategy in digital public services at the Jambi City Public Service Mall (MPP). The research is motivated by the increasing need for integrated, efficient, and transparent public services in the digital era. The purpose of this study is to examine how collaboration between government institutions, the private sector, and the community contributes to the improvement of digital service quality. Using a qualitative approach, data were collected through in-depth interviews, participatory observation, and documentation studies involving various stakeholders. The findings reveal that the application of collaborative governance in the MPP of Jambi City promotes synergy among institutions, enhances transparency, and accelerates service delivery through technological integration such as digital queuing systems and online complaint platforms. However, challenges remain, particularly related to institutional coordination and digital infrastructure readiness. The study concludes that collaborative governance serves as an effective framework for realizing innovative, participatory, and technology-based public services that respond to citizens’ needs efficiently and responsively.